Is amyloid involved in acute neuroinflammation? A CSF analysis in encephalitis. Issue 11 (27th January 2022) - Padovani, Alessandro; Canale, Antonio; Schiavon, Lorenzo; Masciocchi, Stefano; Imarisio, Alberto; Risi, Barbara; Bonzi, Giulio; De Giuli, Valeria; Di Luca, Monica; Ashton, Nicholas J.; Blennow, Kaj; Zetterberg, Henrik; et al.
Abstract: Introduction: Several investigations have argued for a strong relationship between neuroinflammation and amyloid metabolism but it is still unclear whether inflammation exerts a pro‐amyloidogenic effect, amplifies the neurotoxic effect of amyloid, or is protective. Methods: Forty‐two patients with acute encephalitis (ENC) and 18 controls underwent an extended cerebrospinal fluid (CSF) panel of inflammatory, amyloid (Aβ40, 42, and 38, sAPP‐α, sAPP‐β), glial, and neuronal biomarkers. Linear and non‐linear correlations between CSF biomarkers were evaluated studying conditional independence relationships. Results: CSF levels of inflammatory cytokines and neuronal/glial markers were higher in ENC compared to controls, whereas the levels of amyloid‐related markers did not differ. Inflammatory markers were not associated with amyloid markers but exhibited a correlation with glial and neuronal markers in conditional independence analysis. Discussion: By an extensive CSF biomarkers analysis, this study showed that an acute neuroinflammation state, which is associated with glial activation and neuronal damage, does not influence amyloid homeostasis.